2017
DOI: 10.1016/j.foodchem.2017.03.149
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic effect of xylooligosaccharides produced from birchwood xylan by a novel fungal GH11 xylanase

Abstract: A fungal endoxylanase belonging to the glycoside hydrolase gene family 11 (GH11) was obtained from the ascomycete Talaromyces amestolkiae. The enzyme was purified, characterized and used to produce a mixture of xylooligosaccharides (XOS) from birchwood xylan. A notable yield of neutral XOS was obtained (28.8%) upon enzyme treatment and the mixture contained a negligible amount of xylose, having xylobiose, xylotriose and xylotetraose as its main components. The prebiotic potential of this mixture was demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(39 citation statements)
references
References 39 publications
2
34
0
3
Order By: Relevance
“…Chemically, XOS are oligomers with a ramified structure containing 2 to 7 xylose units linked through β-(1,4)-xylosidic bonds and decorated with a diversity of substituents, namely acetyl groups, uronic acids and arabinose units (Kumar & Satyanarayana, 2011). Xylan, the main constituent of hemicelluloses and the second most abundant carbohydrate in the lignocellulosic biomass (Nieto-Domínguez et al, 2017), is the precursor of XOS. Besides the origin of the biomass, the structural features of XOS depend also on the production process (Samanta et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Chemically, XOS are oligomers with a ramified structure containing 2 to 7 xylose units linked through β-(1,4)-xylosidic bonds and decorated with a diversity of substituents, namely acetyl groups, uronic acids and arabinose units (Kumar & Satyanarayana, 2011). Xylan, the main constituent of hemicelluloses and the second most abundant carbohydrate in the lignocellulosic biomass (Nieto-Domínguez et al, 2017), is the precursor of XOS. Besides the origin of the biomass, the structural features of XOS depend also on the production process (Samanta et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Buruiana, Gómez, Vizireanu, and Garrote () reported 11.7 g/L of XOS from corn stover. The extraction of XOS from birchwood xylan yielded 28.8% and was composed mainly of xylobiose, xylotriose, and xylotetraose (Nieto‐Domínguez et al, ).…”
Section: Oligosaccharides As Prebiotic Compoundsmentioning
confidence: 99%
“…In a study performed with fecal microbiota of breast‐fed children, 200 g/L of XOS from birchwood xylan inhibited the increase of the growth of enterobacteria, while 400 g/L lowered their concentration. Additionally, XOS stimulated the growth of probiotic bacteria (Nieto‐Domínguez et al, ). Furthermore, a recent study demonstrated that the pathogenic bacteria Escherichia coli cannot grow in (A)XOS (the mixture of XOS and AXOS) from wheat bran, while L .…”
Section: Oligosaccharides As Prebiotic Compoundsmentioning
confidence: 99%
“…Xylooligosaccharides (XOS) are sugar oligomers containing 2-6 xylose units as high value-added ingredients for functional foods. To date, there is an increasing demand for XOS due to various health benefits such as stimulating the growth of bifidobacteria, lowering cholesterol, increasing mineral adsorption and modulating the immune function (Nieto-Dominguez et al, 2017). Currently, XOS are typically produced by enzymatic approaches using xylan from agro-wastes as raw material (Antov & Dordevic, 2017).…”
Section: Introductionmentioning
confidence: 99%